HUBUNGAN PENGETAHUAN ORANG TUA (IBU) TENTANG TOILET TRAINING TERHADAP KEJADIAN ENURESIS DI TK DHARMA WANITA DESA NGANTRU KECAMATAN NGASEM KABUPATEN BOJONEGORO TAHUN 2017 - UTAMI, WIWIK; Susanti, Dwi Agung; Berliana, Dame (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Enuresis is the normal process of micturition in the place and the time is not right. factors affecting the rate of Enuresis. knowledge of parents about toilet training. The purpose of the research to know relationship between parent knowledge about toilet training against. Enuresis in kinder gartens of Dharma Wanita village Ngantru district Ngasem regency Bojonegoro. Using analytic research approach cross sectional population study of parents who have children of pre-school age totaled 67 respondents and 57 respondents total sample techniques of sampling purposive sampling. Research of variable knowledge of parents and the incidence of Enuresis (bed wetting). Data collection with the editing, coding, skoring and tabulating and analytic analysis results. Results of research most respondents (75.4%) as many as 43 have well knowledge. most respondents (73.7%) as many as 42 did not experience enursis significant value 0.008 < 0.05 so Ho denied showed there is relationship between knowledge parents about toilet training with enuresis There is a relationship between knowledge of parent about toilet training with enuresis in children ages pre school kinder garten in kinder gartens of Dharma Wanita village Ngantru district Ngasem regency Bojonegoro. Expected parents canspend some time doing toilet training since the age of 18 months so be good habits while urinating